LegacyVegetation: Northern Hemisphere reconstruction of past plant cover and total tree cover from pollen archives of the last 14 ka - Ulrike Herzschuh; Peter Ewald; Laura Schild; Chenzhi Li; Thomas Böhmer (PANGAEA, 2025)
This data set presents the reconstructed vegetation cover for 2773 sites based on harmonized pollen data from the data set LegacyPollen 2.0 (https://doi.pangaea.de/10.1594/PANGAEA.965907). 1040 sites are located in North America, 1287 in Europe, and 446 in Asia. Sugita extquotesingles REVEALS model (2007) was applied to all pollen records using REVEALSinR from the DISQOVER package (Theuerkauf et al. 2016). Pollen counts were translated into vegetation cover by accounting for taxon-specific pollen productivity and fall speed. Additionally, relevant source areas of pollen were calculated using the aforementioned taxon-specific parameters and a Gaussian plume model for deposition and dispersal. Values for relative pollen productivity and fall speed from the synthesis from Wiezcorek and Herzschuh (2010) were updated with recent studies used to reconstruct vegetation cover. The average values from all Northern Hemisphere values were used where taxon-specific continental values were unavailable. As REVEALS was conceived to reconstruct vegetation from large lakes, only records originating from large lakes (>= 50h) are marked as "valid as site" in the dataset. Reconstructions from other records can be used when spatially averaging several together. An example script to do so is provided on Zenodo (https://doi.org/10.5281/zenodo.12800290). Reconstructed tree cover was validated using modern Landsat remote sensing forest cover. Reconstructed tree cover has much lower errors than the original arboreal pollen percentages. Reconstructions of individual taxa are more uncertain. We present tables with reconstructed vegetation cover for all continents with original parameters. As further details, we list a table with the taxon-specific parameters used, metadata for all records, and a list of parameters adjusted in the default version of REVEALSinR.